Matematyka
Konto usunięte
32

1. a. (4-2x)-(x+3)=(x-5)+(-3-x) b. (3-2x)+(3x+4)=-(3-2x)+(5x+4) c. -(x+3)+(2x-1)=(1+4x)+(3+x) d. -(x+3)-(2x+8)=(-3-2x)+(2x+1) 2. a. (3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7) b. (4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7) c. (4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6) d. -(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x) 3. a. 3(x-4)-4(2x-7)=2(x+5) b. 2(2x-3)+3(4-x)=-(x+1) c. 2(x-3)-4(3+x)=-3(x+2)+2(2x-1) d. 6(x+1)+3(2-x)=2(2x-1)-(4-x) 4. a.  2(x-7)-3(x+2)=4(x+3)+2(x-9) b. -3(x+6)-6(2x+8)=-2(4-x)+9(x+8) c. -8(x+2)+3(x+5)=-2(2x+3)+4(2x-1) d. 6(4-x)+5(2x-5)=4(x-1)-3(4-x) 5. a. 3(3-x)+2x=8-2(x-1) b. 4x+5-(3x+6)=2(2+x)-4 c. 4-5(3-x)=-x-(3-2x) d. x-(7+2x)=2(x-1)+1

+3
(1) Odpowiedź
popmusic

1. a. (4-2x)-(x+3)=(x-5)+(-3-x) 4-2x-x-3=x-5-3-x 1-3x=-8 -3x=-9 x=3   b. (3-2x)+(3x+4)=-(3-2x)+(5x+4) 3-2x+3x+4=-3+2x+5x+4 7+x=1+7x -6x=-6 x=1   c. -(x+3)+(2x-1)=(1+4x)+(3+x) -x-3+2x-1=1+4x+3+x x-4=4+5x -4x=8 x=-2   d. -(x+3)-(2x+8)=(-3-2x)+(2x+1) -x-3-2x-8=-3-2x+2x+1 -3x-11=-2 -3x=9 x=-3 2. a. (3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7) 3-2x-x-4-2x-5=3x-4-5x-7 -6-5x=-2x-11 -3x=5 x=-[latex]\frac{5}{3}[/latex] x=-1[latex]\frac{2}{3}[/latex]   b. (4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7) 4-x-2x-3+x-4=-2x+3-x-7 -3-2x=-3x-4 x=-1   c. (4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6) 4x-5+x-7-2x+8=-3x+4-x-6 3x-4=-4x-2 7x=2 x=[latex]\frac{2}{7}[/latex]   d. -(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x) -4+2x-2x-4=3x-1+2x-5-7-3x -8=2x-13 -2x=-5 x=[latex]\frac{5}{2}[/latex] x=2[latex]\frac{1}{2}[/latex]   3. a. 3(x-4)-4(2x-7)=2(x+5) 3x-12-8x+28=2x+10 -5x+16=2x+10 -7x=-6 x=[latex]\frac{6}{7}[/latex]   b. 2(2x-3)+3(4-x)=-(x+1) 4x-6+12-3x=-x-1 x+6=-x-1 2x=-7 x=-[latex]\frac{7}{2}[/latex] x=-3[latex]\frac{1}{2}[/latex]   c. 2(x-3)-4(3+x)=-3(x+2)+2(2x-1) 2x-6-12-4x=-3x-6+4x-2 -2x-18=x-8 -3x=10 x=-[latex]\frac{10}{3}[/latex] x-3[latex]\frac{1}{3}[/latex]   d. 6(x+1)+3(2-x)=2(2x-1)-(4-x) 6x+6+6-3x=4x-2-4+x 3x+12=5x-6 -2x=-18 x=9   4. a.  2(x-7)-3(x+2)=4(x+3)+2(x-9) 2x-14-3x-6=4x+12+2x-18 -x-20=6x-6 -7x=14 x=2   b. -3(x+6)-6(2x+8)=-2(4-x)+9(x+8) -3x-18-12x-48=-8+2x+9x+81 -15x-66=11x+73 -26x=139 x=-[latex]\frac{139}{26}[/latex] x=-5[latex]\frac{9}{26}[/latex] c. -8(x+2)+3(x+5)=-2(2x+3)+4(2x-1) -8x-16+3x+15=-4x-6+8x-4 -5x-1=4x-10 -9x=-9 x=1   d. 6(4-x)+5(2x-5)=4(x-1)-3(4-x) 24-6x+10x-25=4x-4-12+3x 4x-1=7x-16 -3x=-15 x=5   5. a. 3(3-x)+2x=8-2(x-1) 9-3x+2x=8-2x+2 9-x=10-2x x=1 b. 4x+5-(3x+6)=2(2+x)-4 4x+5-3x-6=4+2x-4 x-1=2x -x=1 x=-1   c. 4-5(3-x)=-x-(3-2x) 4-15+5x=-x-3+2x -11+5x=x-3 4x=8 x=2   d. x-(7+2x)=2(x-1)+1 x-7-2x=2x-2+1 -x-7=2x-1 -3x=6 x=-2

Dodaj swoją odpowiedź